Motivation and emotional intelligence in secondary physical education classes - Gómez-López, Manuel; Ballester del Cerro, José Antonio; Manzano-Sánchez, David; Granero-Gallegos, Antonio (Revista Complutense de Educación, 2025)
Introduction. Motivation and emotional intelligence are key in today's education. Motivation drives purposeful action, and emotional intelligence reduces frustration, improving the achievement of educational goals. The objectives of the study were to describe and determine the relationship between the level of self-determined motivation and emotional intelligence of secondary school students in physical education classes and to test for gender and age differences in both variables. Method. To this purpose, a total of 607 students between 12 and 18 years of age M = 14.911; DT = .1.46) from three schools in the Region of Murcia participated in the study. Participants were administered the Spanish adaptation of the Sport Motivation Scale-II adapted to Physical Education to measure the individual level of motivation towards Physical Education and the Spanish version of the Trait Meta-Mood Scale to measure perceived emotional intelligence. Results. The main results showed that the most self-determined types of motivation correlated positively with the dimensions of emotional intelligence (attention, clarity and repair). Boys had higher averages than girls in all forms of motivation except amotivation, and also showed higher values for emotional clarity, while girls had higher averages for emotional attention. Discussion. The results are encouraging for this subject, since according to the results and following the literature, most students enjoy learning and participating in class, despite age differences. While boys show a greater understanding of its relevance and benefits, which motivates them to participate more actively for enjoyment, girls tend to pay more attention to their emotions. In conclusion is necessary to promote more internal motivation in order to improve emotional intelligence in secondary education students, especially in girls.
Keywords: emotion; wellbeing; adolescence; intelligence; education